Judaísmo messiânico: cristologia ou messianologia? - Marciano, Marta Rodrigues Alves (2017)
The aim of this dissertation is study the Messianic Judaism, a religious group which is characterized by believing in Yeshua (Jesus, in Hebrew) as the Messiah, while is considered a strand of the Judaism. Since they believe in Yeshua as being Messiah, would they have a Christology? This study contemplates the possibility of distinction in the Messianic Judaism theology, which the major hypothesis is: Messianic Jews have a view in the idea of that Messiah approaches more of Messianology than of a Christology. A qualitative research was conducted on the basis of the literature review on the subject. And for that, were selected as Messianic texts for this analysis the Messianic Jewish Manifest, by Rabbi David Stern and the first two volumes of Jewish Objections Against Jesus, by Rabbi Michael Brown. It was discussed concepts such as dogmatic Christology and Messianology, as this last concept was being proposed by David Flusser in addition to checking the convergences and divergences of the idea of the Messiah for Judaism, Christianity and Messianic Judaism in the first century AD. It was also reported about history of the Messianic-Jewish movement. The collected data throughout this research should be considered to point out to the fact that Messianic-Jewish thought about the Messiah does not seem to correspond to Christological thinking. The main conclusion is that messianology can be understood as key element to build a category that best represents the theological thought of Messanic Judaism